HUBUNGAN DAYA LEDAK OTOT LENGAN DN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN SMASH ATLET BULUTANGKIS PB TERATAK - Riko Darmawan; Iska Noviardila; Vigi Indah Permatha Sari (Jurnal BOLA: Bersama Olahraga Laju Asia, 2023)
This research is based on field observations based on the decline in performance of PB Teratak athletes. It is suspected that the low explosive power of arm muscles and eye-hand coordination possessed by PB Teratak athletes is the background to the problem of this research. The aim of this research was to determine how big the relationship between arm muscle explosive power and eye-hand coordination is on the smash ability of PB Teratak badminton athletes. This research method is correlational research. The research was carried out at PB Teratak in October 2023. The sample for this research was all PB Teratak athletes, totaling 27 people. To measure the explosive power of arm muscles using the Two Hand Medicine Ball-Put, while eye-hand coordination uses a throwing test at a target, and a badminton Smash Ability test. The research results are (1) The explosive power of the arm muscles has a "Quite High" relationship of 0.798 (60,5%) to the smash ability of PB Teratak badminton athletes, (2) Eye-hand coordination has a "High" relationship of 0.823 (67,7%) to the smash ability of PB Teratak badminton athletes, and (3) Arm muscle explosive power and eye-hand coordination together have a "High" relationship of 0.877 (76,9%) to the smash ability of PB Teratak badminton athletes. Thus, the results of this study can be concluded that arm muscle explosive power and eye-hand coordination together have a significant relationship to the smash ability of PB Teratak badminton athletes.